2015
DOI: 10.4172/2151-6219.1000204
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Entrepreneurship in Economic Development in Saudi Arabia

Abstract: One of the key objectives of modern economics is to determine factors that influence the economic development. This paper, therefore, seeks to discuss entrepreneurship as one of the factors that influence the economy of a nation, either directly or indirectly. It is a fact that entrepreneurship plays a significant part in shaping the landscape of a country's economy. Economists and policy makers recognize this fact. In fact, entrepreneurship is the engine of economic growth and it has come to be perceived as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The European Commission [2] considers entrepreneurship as "a process that has the potential to lead to the creation and expansion of firms". Seen as the driver of the society [3][4][5] and one of the main engines of economic growth [6][7][8][9][10], entrepreneurship also plays an important role in increasing communities' living standards [11]. Furthermore, Dejardin [12] suggested that economic growth is faster as the share of innovative entrepreneurs in the labor force increases.…”
Section: Introductionmentioning
confidence: 99%
“…The European Commission [2] considers entrepreneurship as "a process that has the potential to lead to the creation and expansion of firms". Seen as the driver of the society [3][4][5] and one of the main engines of economic growth [6][7][8][9][10], entrepreneurship also plays an important role in increasing communities' living standards [11]. Furthermore, Dejardin [12] suggested that economic growth is faster as the share of innovative entrepreneurs in the labor force increases.…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurship, as an omnipresent aspect of human activity, is the economic engine driving many nations' economies in the global competitive landscape (Fritsch and Wyrwich, 2017;Yusuf and Albanawi, 2016;Toma et.al., 2014;Van Stel et.al., 2005). In the GCC, entrepreneurship is considered as the key plank for economic diversification, employment creation and sustainable growth (Miniaoui and Schilirò, 2017).According to the Economic Development Board (EDB) of Bahrain, the aggregate scale of the importance of SMEs for many countries specifically in the GCC, in terms of generating growth and employment, cannot be underestimated.…”
Section: Introductionmentioning
confidence: 99%